DECREASING VOLUME OF IMAGE DATABASE FOR AUTOMATION FACE RECOGNITION SYSTEM - G. A. Poghosyan (ՀՀ ԳԱԱ հրատ.)
Granting computers ability to discover and identify the object is a contemporary problem that deserves special attention. This problem is widely available in various technological processes, security services, reading systems, criminal law, medical systems, video-conferences, in computer virtual reality, as well as in all video observation systems. Because the recognition database is a collection of images and automatic face recognition system should work with these images, which can hold large volumes of computer memory that is way it’s necessary to investigate and develop a method / tool for optimal using volume of computer memory (that decrease image a database volume) and implement quick search within database.
Keywords: Technology